The Effect of Firm Size and Profitability on Stock Prices (A Case Study of LQ45 Companies for the 2019–2023 Period) - Miftah Faridh Nasir (Sean Institute, 2026)
This study aims to examine the effect of firm size and profitability on stock prices of companies included in the LQ45 listed on the Indonesia Stock Exchange during the 2019-2023 period. The research employs a quantitative approach using secondary data obtained from annual financial statements and stock price reports. The sample was selected using purposive sampling criteria, resulting in panel data observations over five years. Multiple linear regression analysis was applied to test the hypotheses, preceded by classical assumption tests to ensure the validity of the model. The results indicate that firm size has a positive and statistically significant effect on stock prices, suggesting that larger companies tend to have higher market valuations. Profitability, measured by Return on Assets (ROA), also shows a positive and statistically significant effect on stock prices and demonstrates a stronger influence compared to firm size. The simultaneous test confirms that firm size and profitability jointly have a significant impact on stock prices. The coefficient of determination (R²) shows that 37.4% of the variation in stock prices can be explained by the two independent variables, while the remaining 62.6% is influenced by other factors outside the model. These findings imply that investors in the Indonesian capital market place greater emphasis on profitability performance rather than merely company scale when evaluating stocks, particularly during periods of economic disruption and recovery. The study contributes to empirical evidence on the determinants of stock prices in emerging markets and provides practical implications for corporate management in enhancing shareholder value.